Integrasi AI dan Canva for Education untuk Meningkatkan Kompetensi Digital Guru dalam Transformasi Manajemen Pendidikan Sekolah: Integrating AI and Canva for Education to Enhance Teachers' Digital Competence in Transforming School Education Management - Siti Wahyuningsih; Entit Puspita; Ayi Abdurahman (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Digital transformation in education requires teachers to possess technological competencies capable of effectively supporting the learning process and educational management. Artificial Intelligence (AI) and Canva for Education are two technologies increasingly utilised in education to improve teacher work efficiency, learning quality, and instructional media innovation. However, many teachers still lack adequate skills in utilising these two technologies. This community service activity aims to improve teachers' digital competency through a workshop on integrating AI and Canva for Education as an effective educational management strategy. The method used was participatory training involving teachers and principals through lectures, demonstrations, hands-on practice, and mentoring. The workshop, held in collaboration with Nusa Putra University, Sukabumi, spanned three days and covered topics on digital-based education management, the use of AI in teachers' professional duties, and the development of learning media using Canva for Education. The results showed an increase in participants' understanding and skills in using digital technology to support learning and school administration. Participants were able to produce AI-based teaching modules, interactive learning media, educational presentations, and various other digital products. These findings suggest that the integration of AI and Canva for Education can be an alternative solution to improve teachers' digital competency and support the transformation of 21st-century education.